Alteration of cardiovascular autonomic activity in type 2 diabetes mellitus - Gupta, Abhishek; Bhatt, Sukanya; Singhal, Saurabh (International Journal of Research in Medical Sciences, 2019)
Background: Diabetes mellitus (DM) is a clinical syndrome characterized by hyperglycaemia due to absolute or relative insulin deficiency. Cardiovascular autonomic neuropathy (CAN) invokes potentially life-threatening outcomes especially in poorly controlled diabetic patients. This study was to evaluate the prevalence of CAN in diabetic patients and its relationship with QTc interval. Methods: This observational study of two year duration was included total 123 patients of more than 30 (thirty) years and up to 60 (sixty) years of age who were presented with diabetic mellitus (DM) those were evaluated for CAN using four distinct clinical tests-Resting heart rate (RHR), test for orthostatic hypotension (OH), hand gripping test (HGT) and QTc interval on ECG. Data were analyzed with statistical package for social sciences (SPSS), version 23. Results: The mean age of all 103 studied patients was 48.94±8.69 years; Mostly patients belong to 50-60 years of age and the majority was males (69.0%). Out of 103 72.8% patients were reported with CAN (51 males and 24 females) and without CAN were 27.2.0% (20 males and 8 females), 36% of patients of Definite Parasympathetic neuropathy, 25% Normal and 20% of Sympathetic neuropathic patients. HbA1c level increases the danger of CAN also. QTc interval is a reliable indicator for the presence of CAN. Conclusions: Duration of diabetes is directly proportional to the prevalence of CAN. Various cardiac autonomic function tests detect CAN.